Muhammad reconsidered: a Christian perspective on Islamic prophecy - Moreland, Anna Bonta (University of Notre Dame Press, 2020)
Setting the stage -- The state of the question -- Thomas Aquinas on prophecy -- Scriptural prophets and Muhammad: Is Muhammad a prophet for Christians? Joining the conversation -- Closing argument.